Determining measures of effectiveness for New Zealand polytechnics : a thesis presented in partial fulfilment of the requirements of Master of Business Studies, Massey University - Easton, Janet Elizabeth (Massey University, 1995)
This research is a first step toward developing a model which New Zealand polytechnics can use to monitor and measure their own effectiveness. The study breaks new ground in the New Zealand context (which consists of a wide variety of institutions in terms of size, location, and programmes) and extends North American, British and Australian research in the area. The literature review identifies issues in measuring effectiveness, and the strengths and weaknesses of various models used. For this research, a strategic constituencies model was adopted involving major stakeholder groups whose opinions were sought about measuring the effectiveness of their polytechnic. Research subjects were asked to evaluate "Domains of effectiveness" (resulting from prior research) which included: student educational satisfaction; student academic development; student career development; student personal development; staff employment satisfaction; professional development and quality of staff; system openness and community interaction; ability to acquire resources; and organisational health. A tenth domain, social responsibility, was added. Stakeholder opinion on the relevance of these domains for evaluating effectiveness was obtained. They were also asked to rank the importance of each domain from their particular stakeholder stance. No new domains were identified by stakeholders but there is clear evidence that different stakeholders prioritise each domain differently which is in line with the strategic constituencies model of organisational effectiveness. The research provides a framework for other polytechnics to monitor and measure their own effectiveness and a base for further research in these and similar organisations.
Keywords: New Zealand; Education, Higher -- Evaluation; Educational indicators; Technical institutes